2012
DOI: 10.1128/aac.05819-11
|View full text |Cite
|
Sign up to set email alerts
|

Peroral Ciprofloxacin Therapy Impairs the Generation of a Protective Immune Response in a Mouse Model for Salmonella enterica Serovar Typhimurium Diarrhea, while Parenteral Ceftriaxone Therapy Does Not

Abstract: bNontyphoidal Salmonella (NTS) species cause self-limiting diarrhea and sometimes severe disease. Antibiotic treatment is considered only in severe cases and immune-compromised patients. The beneficial effects of antibiotic therapy and the consequences for adaptive immune responses are not well understood. We used a mouse model for Salmonella diarrhea to assess the effects of per os treatment with ciprofloxacin (15 mg/kg of body weight intragastrically 2 times/day, 5 days) or parenteral ceftriaxone (50 mg/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…However, reports of increasing MIC values and subsequent increase in the occurrence of typhoidal salmonellae resistant to ciprofloxacin suggest that it will not remain effective for much longer [20,21]. Furthermore, extended-spectrum cephalosporins such as ceftriaxone are now being used specially for treating children [22,23]. These therapeutic failures have prompted lively research on possible synergism of 27 mm f cefo (20 lg/ml): 20 mm g cryptdin-2 (10 lg/ml) ?…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of increasing MIC values and subsequent increase in the occurrence of typhoidal salmonellae resistant to ciprofloxacin suggest that it will not remain effective for much longer [20,21]. Furthermore, extended-spectrum cephalosporins such as ceftriaxone are now being used specially for treating children [22,23]. These therapeutic failures have prompted lively research on possible synergism of 27 mm f cefo (20 lg/ml): 20 mm g cryptdin-2 (10 lg/ml) ?…”
Section: Discussionmentioning
confidence: 99%
“…The SPI2-TTSS deficient Salmonella Typhimurium strain has already been established as safe vaccine [13], [14]. Though it gives protective mucosal immunity in C57BL/6 mice but it causes lethal infections in various isogenic immunocompromised mice in our experiments.…”
Section: Resultsmentioning
confidence: 71%
“…Typhimurium ssaV mutant, showed O-antigen specific responses and were protected from subsequent S . Typhimurium challenge infections [13], [14]. However, in this study, introduction of S. Typhimurium SPI2-T3SS mutant to immune-compromised mice (IL10 −/− , CD40L −/− , iNos −/− ) indicated that the mutant deficient in T3SS-II is not safe enough and caused lethal infections.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Moon et al [97] demonstrated that certain species in the intestinal microbiota can degrade the secretory component of sIgA and thereby reduce the levels of total intestinal sIgA. Further, there are numerous studies suggesting that antibiotic treatment either enhances or inhibits the response to oral vaccines [98][99][100]. The variation observed may be due to a highly complex interplay between live-attenuated strains that are differentially susceptible to antibiotics, differential depletion of microbiota constituents, and direct side-effects of certain antibiotics on mammalian cells.…”
Section: The Tendency Of Antigen To Reach Galt: the Role Of Pre-existmentioning
confidence: 99%